Pengaruh Pemberian Aromatherapy Eucalyptus Terhadap Mual Muntah Pasien Kanker Payudara Pasca Kemoterapi Di RSUD Dr. Moewardi Surakarta - Novica Indriyani; Anis Ardiyanti; Diffa Risqa Arisdiani (Jurnal Ilmiah Kedokteran dan Kesehatan, 2023)
Breast cancer is a type of malignant cancer that requires chemotherapy, chemotherapy has one effect, one of which is nausea and vomiting. Nausea and vomiting can be overcome with eucalyptus aromatherapy. The purpose of this study was to determine the effect of eucalyptus aromatherapy on nausea and vomiting in post-chemotherapy breast cancer patients. This research method uses a pre-experimental pretest and posttest one group design. The sampling technique used was purposive sampling on 62 respondents, using the INVR measuring instrument. The results of the analysis obtained the majority of age 41.9%, education 46.8% and employment status 48.4%. The vomiting rate of post-chemotherapy patients before being given the intervention was moderate nausea and vomiting 53.2% and after giving eucalyptus aromatherapy 45.2% after that the Wilcoxon statistical test was carried out, so that the p value of nausea was 0.000 <0.05. The conclusion is that there is an effect of giving eucalyptus aromatherapy on nausea and vomiting in post-chemotherapy breast cancer patients. Suggestions for future researchers can be used as a reference for future researchers and pay more attention to the time of giving eucalyptus aromatherapy so that it can be optimal